Information disorder’s impact on adolescents: publication trends and recommendations - Irwanto, Irwanto; Bahfiarti, Tuti; Unde, Andi Alimuddin; Sonni, Alem Febri (Frontiers in Communication, 2025)
The spread of information disorder on social media has become a significant concern, especially regarding its impact on adolescents, with consequences affecting their cognitive development, social interactions, and decision-making abilities. This study aimed to analyze trends and patterns in scholarly publications related to social media information disorder and its impact on adolescents by mapping the current landscape of studies, identifying key contributors, and highlighting emerging themes. A bibliometric approach used data from the SCOPUS database, which was cleaned and analyzed using various methods, including visualization with VOSviewer, covering publication trends, citation analysis, collaboration networks, and keyword clustering. The results showed a significant annual increase in publications, indicating growing academic interest, with the United States emerging as a major contributor, followed by other developed and developing countries. Citation analysis revealed influential works that shaped the discourse, network visualization illustrated patterns of researcher collaboration, and keyword analysis identified key clusters, such as disinformation and adolescents, media literacy, the role of social media, and the impact of the COVID-19 pandemic on information dissemination. Impacts on adolescents include impaired critical thinking skills, increased vulnerability to manipulation, potential social and political polarization, negative effects on mental health and self-esteem, and challenges in distinguishing credible information from false or misleading information. This research emphasizes the need for comprehensive literacy strategies, international collaboration, and culturally sensitive approaches to address the challenges posed by information disorder in adolescents, highlights the importance of cross-culturally integrated solutions to empower youth in the digital age, and provides valuable insights for future research.